Implementation of Sky Parenting in Educating Children to Increase Interest in Reading: A Case Study of A Muslim Family in Balai Baru Kuranji Padang West Sumatra - Agustina, Linda; Tago, Mahli Zainuddin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study examines parental care's impact on implementing child prayer discipline. The discipline of prayer includes technical aspects of worship and a strong understanding and commitment to religious values. Through a qualitative approach, this study highlights the positive role of sky parenting in stimulating children's interest in reading through the introduction of religious reading materials and examples of parents who love spiritual literature. This research is located in Balai Baru Kuranji, Padang, West Sumatra. After collecting the data, the research analysis stage begins with data categorization and coding to identify emerging patterns and themes related to sky parenting practices and educate children to incrase interest in reading. Furthermore, this study uses a thematic analysis approach to explore the relationship between sky parenting practices and educating children to incrase interest in reading. Finally, the study compiles the findings into a coherent narrative and produces conclusions. The scope of this research includes several key aspects: (1) Identification of Sky Parenting strategies and techniques applied by the family in educating children, (2) Analysis of the impact of the application of Sky Parenting on children's interest in reading, (3) Factors that support and hinder the success of this method, and (4) The role of Islamic values in the implementation of Sky Parenting. The conclusion of this study reinforces that sky parenting, with a focus on spiritual education, can be an effective strategy in increasing children's interest in reading, opening opportunities for better religious literacy development in the future. The practical implications of this research can provide valuable guidance for educators, parents, and communities to strengthen children's literacy by applying sky-parenting principles.